INDUSTRY 4.0+ AND THE FACTORY OF THE FUTURE: TOWARD INTELLIGENT, FLEXIBLE, AND SUSTAINABLE MANUFACTURING: INDUSTRY 4.0+ AND THE FACTORY OF THE FUTURE: TOWARD INTELLIGENT, FLEXIBLE, AND SUSTAINABLE MANUFACTURING - Vasilev, Dragomir (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
The continuous evolution of industrial systems marks the transition from conventional automation toward intelligent, adaptive, and networked manufacturing ecosystems, collectively known as Industry 4.0. This transformation integrates cyber-physical systems (CPS), artificial intelligence (AI), and the Internet of Things (IoT) to create highly flexible, efficient, and responsive production environments. With the rapid advancement of 5G and the emerging 6G communication technologies, a new phase of industrial development—Industry 4.0+—is envisioned. This next-generation paradigm emphasizes ultra-low latency, machine-to-machine communication, predictive maintenance, and collaborative automation, enabling a fully connected and self-optimizing industrial environment. The paper explores the technological foundations, core principles, and practical implications of Industry 4.0+, focusing on wireless communication, motion control, AI-driven robotics, sustainability, and collective automation in the factory of the future.